(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2010)
Oxcarbazepine (OXC) is an important anticonvulsant and mood stabilizing drug. A pharmacopoeial monograph for OXC is not yet available and therefore the development and validation of a new analytical method for quantification of this drug is essential. In the present study, a UV spectrophotometric method for the determination of OXC was developed. The various parameters, such as linearity, precision, accuracy and specificity, were studied according to International Conference on Harmonization Guidelines. Batches of 150 mg OXC capsules were prepared and analyzed using the validated UV method. The formulations were also evaluated for parameters including drug-excipient compatibility, flowability, uniformity of weight, disintegration time, assay, uniformity of content and the amount of drug dissolved during the first hour.